ANALISIS KEBUTUHAN E – LKPD INTERAKTIF MATERI MAJAS BERBASIS MODEL KOOPERATIF TIPE MAKE A MATCH DI SD - Setiawaty, Rani; Fadhilah , Wiwit Syafa’atul; Khoirunnisa , Ony Khansa'; Ardayanti , Melysa Dwi; Maknun, Lu’lu’ul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the need for developing interactive E-LKPD (Electronic Learning and Teaching Materials) on hyperbole based on the Make a Match cooperative model in grade V of SD Negeri 1 Gulang. The underlying problem of this study is that the learning process of hyperbole still tends to use printed LKPD that is monotonous, less interactive, and ineffective in helping students understand the abstract concept of hyperbole. This situation has an impact on the low level of mastery and participation of students in Indonesian language lessons as well as the limitations of teachers in creating new and innovative digital learning media. This study used a qualitative approach with a case study design. The subjects in this study consisted of one fifth-grade teacher and 30 students. Data collection techniques included interviews, questionnaires, and document analysis, while data analysis followed the model designed by Miles and Huberman, which included data reduction, data presentation, and conclusion drawing. The findings of this study indicate that both teachers and students have a high need for interactive E-LKPD equipped with images, colors, animations, and interactive exercises based on the Make a Match model. The availability of digital facilities and infrastructure in schools also supports the implementation of interactive E-LKPD. Thus, the development of interactive E-LKPD based on the Make a Match model is considered vital and appropriate for improving